South Korea as a middle power: A Systemic Impact approach / Tan Yi-Zhong - Tan , Yi-Zhong (2019)
This research evaluated whether South Korea is a ‘middle power’ by using the ‘systemic impact’ approach. The term ‘middle power’ has a long history, going back all the way to 15th century in Italy, Europe (Yama, 2009). However, it was only in the 20th century when the term ‘middle power’ rose to prominence in the study of international relations. It was during this time that different scholars put forth different approaches as to how a country can be evaluated as to determine whether it is a ‘middle power’ or not. Although South Korea has been classified as a ‘middle power’ by scholars and South Korean politicians alike in the last two decades, this study has discovered that South Korea’s position as a ‘middle power’ is rather vague. This is because there is still no universally accepted approach/method on how to evaluate whether a country is a ‘middle power’ by scholars, despite efforts made by scholars over the years. Therefore, there is a level of uncertainty on the status of countries categorised as a ‘middle power’, as a country can be considered a ‘middle power’ using one approach but not another. In response to the problem, the Australian scholar Andrew Carr (2014) presented the ‘systemic impact’ approach, a comprehensive approach to evaluating ‘middle power’. Carr originally utilised the ‘systemic impact’ approach to prove that Australia, which was categorised as a ‘middle power’ for decades, was indeed a ‘middle power. In the same vein, this study will utilise Carr’s ‘systemic impact’ approach to determine whether South Korea, who has been classified as a ‘middle power’ for close to two decades, is indeed a ‘middle power’ or not.